Egg Yolk IgY: A Novel Trend of Feed Additives to Limit Drugs and to Improve Poultry Meat Quality - Hussein, Mohamed A.; Rehan, Ibrahim F.; Rehan, Ahmed F.; Eleiwa, Nesreen Z.; Abdel-Rahman, Mootaz A. M.; Fahmy, Sohaila G.; Ahmed, Ahmed S.; Youssef, Mohammed; Diab, Hassan M.; Batiha, Gaber E.; Alrashood, Sara T.; Khan, Haseeb A.; et al. (Frontiers in Veterinary Science, 2020)
Drugs commonly used in poultry farms can potentially cause a detrimental effect on meat consumers as a result of chemical residues. Therefore, seeking a natural alternative is crucial for the health of consumers. The egg yolk immunoglobulin Y (IgY) is a promising a natural replacement for antibiotics in the broilers' diet. There is a scarce focusing on the influence of probiotics and IgY on the quality and nutritive values of broilers’ meat and whether it can efficiently displace the anti-microbial power of antibiotics. Herein, we used forty Ross chicks (1.2 ± 0.43 day old) and separate them into four groups with variant feed additives (basal diet "control", probiotic, IgY, and probiotic + IgY). Our findings showed that the combination group of probiotic and IgY supplementation enhanced carcasses quality traits and decreased the pH values that could retard spoilage bacteria and improve shelf life and meat quality. Also, the same group achieved a significant reduction in the thiobarbituric acid value, indicating an improvement of meat quality. Moreover, color, shear force, water holding capacity, and cooking loss were most accepted in broiler meat supplemented with IgY which confirmed the highest carcass quality. Notably, the weight gain in the combination group has been greatly increased. Also, the protein percentage was the highest (22.26 ± 0.29, P < 0.001) in this combined one which revealed the highest nutritive values. Staphylococcus aureus and Escherichia coli could not be detected in the meat of the probiotic group and/or in the combinated one. Interestingly, the IgY group showed an evidence of the killing power (Log CFU/ ml) of Staphylococcus aureus and Listeria monocytogenes at 1500 µg/ ml. Our findings, in vitro as well as in vivo, revealed that the combination group had antimicrobial bioactivity and enhanced the chickens' immunity. Therefore, IgY, a novel trend of feed additives, can be used to limit drugs. Additionally, the morality percentage recorded zero in all groups received feed supplementations while the combined one reached the best financial advantages. We concluded that feeding IgY-powder with probiotic is a frontier to improve the productivity, immunity, and meat quality of broilers.